2008
DOI: 10.1111/j.1365-2745.2008.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Local escape of an invasive plant, common ragweed (Ambrosia artemisiifolia L.), from above‐ground and below‐ground enemies in its native area

Abstract: Summary 1.The Enemy Release Hypothesis proposes that exotic species gain an advantage in new regions because their natural enemies are lost during invasion; however, enemy release could also occur as a result of much smaller scale movements within an invasive plant's native range, i.e. if it escapes enemies while colonizing new sites. Few studies have considered this possibility, and none has compared escape from multiple guilds of enemies. 2. We studied an invasive North American weed, Ambrosia artemisiifolia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 70 publications
2
34
1
Order By: Relevance
“…This result indicates that soil pathogens' effect on studied species dominated over the effect of soil microbial mutualists. Our results agree with the findings of Agrawal et al (2005) and van Grunsven et al (2007), whereas MacKay and Kotanen (2008) or Callaway et al (2004) showed that symbionts were the dominant component of the soil microbiota. Unfortunately, we cannot say which species or even guilds of soil microbiota were responsible for the observed pattern.…”
Section: Discussionsupporting
confidence: 93%
“…This result indicates that soil pathogens' effect on studied species dominated over the effect of soil microbial mutualists. Our results agree with the findings of Agrawal et al (2005) and van Grunsven et al (2007), whereas MacKay and Kotanen (2008) or Callaway et al (2004) showed that symbionts were the dominant component of the soil microbiota. Unfortunately, we cannot say which species or even guilds of soil microbiota were responsible for the observed pattern.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies that have examined the influence of soil biota on species performance have found that interactions with natural enemies in the soil are generally more pronounced in species' native ranges (e.g. Klironomos 2002;Reinhart et al 2003;Reinhart & Callaway 2006), particularly in association with conspecifics (MacKay & Kotanen 2008). However, we found that positive interactions dominated seedling performance, since seedling growth in the treatment soils was considerably higher than in the sterile control soils.…”
Section: R H I Z O B I a L A V A I L A B I L I T Y L I M I T S P L A contrasting
confidence: 64%
“…These genes have a role in producing secondary metabolites and stress tolerance, as well as in degradation of xenobiotics (Hodgins et al, 2013 . After having been settled in Europe, ragweed spread quickly, since herbivorous and granivorous species harrmful for A. artemisiifolia in its homeland were missing from Europe (Mackay and Kotanen, 2008).…”
Section: Distribution Of Ragweed In Europementioning
confidence: 99%